Dubious use or misuse of scientific information in commerce and policy making e.g. the swim suit case - Clarys, J. P.; Scafoglieri, A.; Tesignie, J.; Cattrysse, E. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Regardless the active resistance data acquisition variance between the Marine Test Station (BrusselsWageningen) data, the Swimming Flume (Stockholm) findings, the Measuring Active Drag (MAOAmsterdam), the device for measuring active drag (DAD-Beijing) or the Velocity Perturbation Method (VPM), these approaches do not interfere with the direct obtained values of passive drag e.g. Ds versus Dp and with our laminar and turbulent flow knowledge. The aim of this project is to reevaluate resistance data of the end of previous century in combination with interpretations of the High-Technology swimwear studies (2000-2010). Commercial justifications of Drag-versus morphology data versus the non-dimensional form relation, have been ignored. The continuous body shape deformations at Ds level are subject of a violation of basic hydrodynamic reasoning. The impressive quantity of records with the High-Tech swimwear was probably a sufficient argumenteven misleading-to accept all quality issues claimed by the manufacturer. But why ban High-Tech swimwear which facilitates movement only e.g. the fascia theory. In cycling the aerodynamic outfit and bike design improve performance at a level of seconds and minutes over distance. Nor the High-Tech swimwear, nor the aerodynamics hardware in cycling do overrule the individuals training and performance effort. Dubious argument acceptance or discriminating morality?